2015
DOI: 10.1177/1933719114529376
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Miscarriage and Micro-RNA Among North Indian Women

Abstract: Micro-RNAs (miRNAs) regulate diverse cellular processes such as cell differentiation, proliferation and apoptosis. Mutation in miRNAs results in various pathological conditions such as inflammation, viral infections, neurodegeneration, autoimmunity, and so on. We have evaluated the association of miR-146aC > G (rs2910164), miR-149T > C (rs2292832), miR-196a2T > C (rs11614913), and miR-499A > G (rs3746444) among patients with recurrent miscarriage (RM) and controls from North India. All the 200 patients with RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
3
19
1
Order By: Relevance
“…Importantly, similar to the miR196a2, we did not find a positive significant association between miR499 polymorphism the increased risk of RPL compared to control group. A similarity to our findings, Parveen et al, recorded that miR-499 A > G gene polymorphism considerably significantly elevated risk in the patients with RPL compared to the controls (19). In addition, Jeon et al, was ascertained the combination of miR196a2CC and miR-499AG + GG synergistic effects to RPL (12).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, similar to the miR196a2, we did not find a positive significant association between miR499 polymorphism the increased risk of RPL compared to control group. A similarity to our findings, Parveen et al, recorded that miR-499 A > G gene polymorphism considerably significantly elevated risk in the patients with RPL compared to the controls (19). In addition, Jeon et al, was ascertained the combination of miR196a2CC and miR-499AG + GG synergistic effects to RPL (12).…”
Section: Discussionsupporting
confidence: 91%
“…Contradictory to our results, Jeon et al, reported significantly different frequencies of the miR-196a2 CC in the patients compared to control group (12). Similarity, Parveen et al, assessed the potential of the risk of miR-196a2 polymorphism between women suffering from of unexplained RPL and normal group in the North Indian women, which was disclosed as an increased risk in allelic level in miR-196a2 T > C of RPL (19). In addition, Jeon et al, adjusted this nucleotide variation in the aborted embryones, and the findings showed the significantly different frequency of the miR-196a2 CC genotypes compared with control subjects (4).…”
Section: Discussionsupporting
confidence: 84%
“…It is well worth mentioning that miRNA are non-coding RNAs that mediate transcription and degradation of mRNA. Although there are currently few related studies, attempting to clarify the association between miRNA mutant and RM may provide a new approach for the exploration of RM etiology (26,27). Genetic polymorphisms directly or indirectly related to coagulation or fibrinolysis processes have also been widely studied in association with RM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown a link between abortion and breast cancer risk, and induced abortion may be a risk factor for breast cancer. [9][10][11] Therefore, it is helpful to understand the causes of RM by studying whether some genes involved in breast cancer pathogenesis are associated with RM. 8 In addition, other studies have shown that certain genetic polymorphisms are associated with breast cancer and may also be related to abortion, for example, the MDM2 Del1518 polymorphism and miR-196a (rs11614913).…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, other studies have shown that certain genetic polymorphisms are associated with breast cancer and may also be related to abortion, for example, the MDM2 Del1518 polymorphism and miR-196a (rs11614913). [9][10][11] Therefore, it is helpful to understand the causes of RM by studying whether some genes involved in breast cancer pathogenesis are associated with RM.…”
Section: Introductionmentioning
confidence: 99%